Control of Salmonella Enteritidis and Salmonella Gallinarum in birds by using live vaccine candidate containing attenuated Salmonella Gallinarum mutant strain - Casarin Penha Filho, Rafael Antonio [UNESP]; de Paiva, Jacqueline Boldrin; da Silva, Mariana Dias; de Almeida, Adriana Maria; Berchieri Junior, Angelo (Elsevier B.V., 2010)
The ideal ideal live vaccine to control Salmonella in commercial chicken flocks should engender protection against various strains. The purpose of the present study was to confirm the attenuation of a Salmonella Gallinarum (SG) mutant strain with deletion on genes cobS and cbiA, that are involved in the biosynthesis of cobalamin. Furthermore, evaluate its use as a live vaccine against Salmonella. For the evaluation of the vaccine efficacy, two experiments were conducted separately. Birds from a commercial brown line of chickens were used to perform challenge with SG wild type strain and birds from a commercial white line of chickens were used to perform challenge with Salmonella Enteritidis (SE) wild type strain. In both experiments, the birds were separated in three groups (A, B and C). Birds were orally vaccinated with the SG mutant as the following programme: group A, one dose at 5 days of age; group B, one dose at 5 days of age and a second dose at 25 days of age; and group C, birds were kept unvaccinated as controls. At 45 days of age, birds from all groups, including the control, were challenged orally by SG wild type (brown line) or SE wild type (white line). Lastly, another experiment was performed to evaluate the use of the SG mutant strain to prevent caecal colonization by SE wild type on 1-day-old broiler chicks. Mortality and systemic infection by SG wild type strain were assessed in brown chickens; faecal shedding and systemic infection by SE wild type were assessed in white chickens and caecal colonization was assessed in broiler chicks. Either vaccination with one or two doses of SG mutant, were capable to protect brown chickens against SG wild type. In the experiment with white chickens, only vaccination with two doses of SG mutant protected the birds against challenge with SE wild type. Although, SG mutant could not prevent caecal colonization in 1-day-old broiler chicks by the challenge strain SE wild type. Overall, the results indicated that SG mutant is a promising Salmonella live vaccine candidate that demonstrated good efficacy to control the infection by two serotypes of major importance to the poultry industry. (c) 2010 Elsevier Ltd. All rights reserved.
Keywords: Salmonella Gallinarum; Salmonella Enteritidis; Live vaccine; Cobalamin mutant